2017
DOI: 10.1101/225516
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Automated detection of sleep-boundary times using wrist-worn accelerometry

Abstract: Objective Current polysomnography-validated measures of sleep status from wrist-worn accelerometers cannot be used in fully automated analysis as they rely on self-reported sleep-onset and -end (sleep-boundary) information. We set out to develop an automated, data-driven approach to sleep-boundary detection from wrist-worn accelerometer data. MethodsOn three separate occasions, participants were asked to wear a GENEActiv ® wrist-worn accelerometer for nine days and concurrently complete sleep diaries with ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Our findings of the reasons for outlier values were in line with previous research [ 42 ], which have indicated that low activity before bedtime or after wake-up time makes it difficult to detect sleep period from the acceleration data. Also, wakefulness during the night was reported as a challenge in sleep duration detection from acceleration data [ 32 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings of the reasons for outlier values were in line with previous research [ 42 ], which have indicated that low activity before bedtime or after wake-up time makes it difficult to detect sleep period from the acceleration data. Also, wakefulness during the night was reported as a challenge in sleep duration detection from acceleration data [ 32 ].…”
Section: Discussionsupporting
confidence: 91%
“…Also, wakefulness during the night was reported as a challenge in sleep duration detection from acceleration data [ 32 ]. O’Donnell and colleagues have discussed that errors in self-reporting were a reason for the outliers [ 42 ]. Sleep period detection with a wearable device such as Polar Active or Ōura ring happens without any actions by the user, unlike in sleep diaries.…”
Section: Discussionmentioning
confidence: 99%
“…Another strength was that both wrist acceleration and PAEE was assessed simultaneously, thus providing more accurate stratification by PAEE levels; however a limitation of our work is that we only measured physical activity during one week of monitoring, and this may not be representative of habitual behavior in this population. Another potential limitation is the separation between static and dynamic wrist acceleration; as has been previously addressed, the highand low-pass filter parameters does not perfectly discriminate between static and dynamic and a small proportion of real movement will be missed during rapid rotations (O'Donnell et al, 2017). Nonetheless, this is likely to only bias the movement differences we observe towards the null, since younger and slimmer individuals are more able to produce more rapid movements, and it will likely not impact much on the postural measures, as the gravitational acceleration component is several orders of magnitude larger than residual movement in the lowpass filtered signal, thus still returning a valid estimate of the relative distribution of gravity in the three axes.…”
Section: Discussionmentioning
confidence: 99%
“…Another strength was that both wrist acceleration and PAEE was assessed simultaneously, thus providing more accurate stratification by PAEE levels; however a limitation of our work is that we only measured physical activity during one week of monitoring, and this may not be representative of habitual behaviour in this population. Another potential limitation is the separation between static and dynamic wrist acceleration; as has been previously addressed, the high-and low-pass filter parameters does not perfectly discriminate between static and dynamic and a small proportion of real movement will be missed during rapid rotations (34). Nonetheless, this is likely to only bias the movement differences we observe towards the null, since younger and slimmer individuals are more able to produce more rapid movements, and it will likely not impact much on the postural measures, as the gravitational acceleration component is several orders of magnitude larger than residual movement in the low-pass filtered signal, thus still returning a valid estimate of the relative distribution of gravity in the three axes.…”
Section: Discussionmentioning
confidence: 99%